2015
DOI: 10.1016/j.ijid.2014.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Association of the CYP2B6 gene with anti-tuberculosis drug-induced hepatotoxicity in a Brazilian Amazon population

Abstract: The G516T polymorphism in the CYP2B6 gene is a key predictor of the therapeutic response to treatment in TB patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
(34 reference statements)
0
17
0
Order By: Relevance
“…The frequency of the polymorphic allele previously determined for individuals in the city of Belé m who were receiving treatment for tuberculosis (0.30) is similar to the frequency found in the present study (0.36). 33 Knowing the frequency distribution of the allele among different ethnic groups will improve our knowledge, evaluation, and understanding of the consequences of genetic variation, especially with regard to the influence of the response to treatment for infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of the polymorphic allele previously determined for individuals in the city of Belé m who were receiving treatment for tuberculosis (0.30) is similar to the frequency found in the present study (0.36). 33 Knowing the frequency distribution of the allele among different ethnic groups will improve our knowledge, evaluation, and understanding of the consequences of genetic variation, especially with regard to the influence of the response to treatment for infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, two previous studies reported a subtle increase of EFV plasma concentration in African and African-American patients following EFV-rifampicin treatment (Gengiah et al, 2012;Luetkemeyer et al, 2013). Co-administration of first-line TB drugs are associated with drug induced hepatotoxicity (Xiang et al, 2014;Yimer et al, 2011;Fernandes et al, 2015) Rifampicin (RMP) and Isoniazid (INH) are widely used combination regimens and were shown to associate with hepatotoxicity in TB patients with CYP2B6 c.516TT genotype (Fernandes et al, 2015). In this context, our findings suggest that 40% (8/20) of participants (CYP2B6 c.516TT) with HIV-1 + TB co-infection in this study may likely develop drug induced hepatotoxicity if RMP and INH are administered together.…”
Section: Discussionmentioning
confidence: 99%
“…CYP2B6 is also involved in the metabolism of RMP and INH (Yimer et al, 2011). The CYP2B6 c.516G>T polymorphism was shown to modulate the TB therapeutic response (Fernandes et al, 2015). The CYP2B6 c.516G>T has been associated with an increased plasma exposure to EFV (Cortes et al, 2013;Sinxadi et al, 2015;Swart et al, 2013) and increased risk of toxicity in the CNS (Aurpibul et al, 2012;Martin et al, 2014;Sinxadi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…P4HB, a disulfate enzyme catalyzation, increased the Th-2 cell migration. In addition, the active compounds not only interacted with protein-related immunity but also another protein like CYP2B6, a cytochrome 450 enzyme, which could be an indicator for tuberculosis therapy [25].…”
Section: Interaction Between Active Compounds Of Indonesian Medicinalmentioning
confidence: 99%